Minat Siswa Mengikuti Pesantren Kilat di SMK Negeri 1 Pantai Labu Tahun 2019 - Dalimunthe, Rasyid Anwar (Sekolah Tinggi Agam Islam Sumatera Medan, 2020)
This study aims to find out how students' interest in participating in Islamic boarding schools in the Koran material, how students' interest in participating in Islamic boarding schools in question and answer material about Islam, and how students' interest in participating in boarding schools in the material to pray according to the demands of the Qur'an and Hadith. This study uses a qualitative method based on descriptive stution. The results showed that students' interest in participating in the Pesantren Kilat program with the material to study the Qur’an was in the category of very good (72.5%). Then the interest of students in participating in the boarding school program flash with question and answer about Islam is also in the very good category (87.5%). Then the interest of students in following the flash boarding program with material on how to carry out prayer according to the guidance of the Qur’a and hadiths is in the very good category too (52.5%). From these results it appears that the highest interest is in the question and answer activity around Islam, this activity is indeed in demand by students because of their interest in current issues surrounding Islamic problems.